Prussian Blue Nanoparticles as a Catalytic Label in a Sandwich Nanozyme-Linked Immunosorbent Assay - Farka, Zdeněk; Čunderlová, Veronika; Horáčková, Veronika; Pastucha, Matěj; Mikušová, Zuzana; Hlaváček, Antonín; Skládal, Petr (Analytical chemistry, 2018)
Enzyme immunoassays are widely used for detection of analytes within various samples. However, enzymes as labels suffer several disadvantages such as high production cost and limited stability. Catalytic nanoparticles (nanozymes) can be used as an alternative label in immunoassays overcoming the inherent disadvantages of enzymes. Prussian blue nanoparticles (PBNPs) are nanozymes composed of the Fe4[Fe(CN)6]3-based coordination polymer. They reveal peroxidase-like activity and are capable of catalyzing the oxidation of colorless 3,3',5,5'-tetramethylbenzidine in the presence of H2O2 to form intensely blue product. Here, we introduce the method for conjugation of PBNPs with antibodies and their application in nanozyme-linked immunosorbent assay (NLISA). Sandwich NLISA for detection of human serum albumin in urine was developed with limit of detection (LOD) of 1.2 ng·mL-1 and working range up to 1 μg·mL-1. Furthermore, the microbial contamination of Salmonella Typhimurium in powdered milk was detected with LOD of 6 × 103 colony-forming units (cfu)·mL-1 and working range up to 106 cfu·mL-1. In both cases, a critical comparison with the same immunoassay but using native peroxidase as label was realized. The achieved results confirmed the suitability of PBNPs for universal and robust replacement of enzyme labels.
Keywords: protilátky bakteriální; Animals; Catalysis; Immunosorbent Techniques; katalýza; Nanoparticles; lidé; Ferrocyanides; Serum Albumin, Human; nanočástice; lidský sérový albumin; Biosensing Techniques; Milk; Antibodies, Bacterial; ferrokyanidy; imunosorpční techniky; Salmonella typhimurium; limita detekce; biosenzitivní techniky; Limit of Detection; zvířata; mléko; Humans